B-Lymphocyte Phenotype Determines T-Lymphocyte Subset Differentiation in Autoimmune Diabetes - Egia-Mendikute, Leire; Arpa, Berta; Rosell-Mases, Estela; Corral-Pujol, Marta; Carrascal, Jorge; Carrillo, Jorge; Mora, Conchi; Chapman, Harold; Panosa, Anaïs; Vives-Pi, Marta; Stratmann, Thomas; Serreze, David; et al. (Frontiers in Immunology, 2019)
Previous studies indicate that B-lymphocytes play a key role activating diabetogenic T-lymphocytes during the development of autoimmune diabetes .Recently, two transgenic NOD mouse models were generated: the NOD-PerIg and the 116C-NOD mice. In NOD-PerIg mice, B-lymphocytes acquire an activated proliferative phenotype and support accelerated autoimmune diabetes development. In contrast, in 116C-NOD mice, B-lymphocytes display an anergic-like phenotype delaying autoimmune diabetes onset and decreasing disease incidence. The present study further evaluates the T- and B-lymphocyte phenotype in both models. In islet-infiltrating B-lymphocytes (IIBLs) from 116C-NOD mice, the expression of H2-Kd and H2-Ag7 is decreased, whereas that of BAFF, BAFF-R, and TACI is increased. In contrast, IIBLs from NOD-PerIg show an increase in CD86 and FAS expression. In addition, islet-infiltrating T-lymphocytes (IITLs) from NOD-PerIg mice exhibit an increase in PD-1 expression. Moreover, proliferation assays indicate a high capacity of B-lymphocytes from NOD-PerIg mice to secrete high amounts of cytokines and induce T-lymphocyte activation compared to 116C B-lymphocytes. This functional variability between 116C and PerIg B-lymphocytes ultimately results in differences in the ability to shape T-lymphocyte phenotype. These results support the role of B-lymphocytes as key regulators of T-lymphocytes in autoimmune diabetes and provide essential information on the phenotypic characteristics of the T- and B-lymphocytes involved in the autoimmune response in autoimmune diabetes.